2007
DOI: 10.1002/pssc.200675858
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation in three zirconia polymorphs

Abstract: Positron lifetimes and high momentum profiles both for the perfect lattice and selected defects are calculated in three (cubic, tetragonal and monoclinic) zirconia polymorphs using the atomic superposition method. Theoretical data are compared with the measured positron lifetime for cubic and tetragonal monocrystals of yttria-stabilized zirconia (YSZ) and coincidence Doppler broadening measurements on tetragonal monocrystals of YSZ. Positron lifetime spectra of YSZ monocrystals exhibit a single component spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
6
21
0
Order By: Relevance
“…On the other hand, the interpretation of lifetime τ 1 , observed for the monocrystalline specimens, as that of free positrons in the bulk is not straightforward. As shown in our recent study [10], slightly shorter bulk lifetimes are suggested by theoretical calculations for zirconia polymorphs. A more open-space structure of the lattice due to the non-stoichiometry-introduced oxygen vacancies in the YSZ system was ibidem tentatively considered as a possible cause for such a discrepancy.…”
Section: Resultssupporting
confidence: 69%
“…On the other hand, the interpretation of lifetime τ 1 , observed for the monocrystalline specimens, as that of free positrons in the bulk is not straightforward. As shown in our recent study [10], slightly shorter bulk lifetimes are suggested by theoretical calculations for zirconia polymorphs. A more open-space structure of the lattice due to the non-stoichiometry-introduced oxygen vacancies in the YSZ system was ibidem tentatively considered as a possible cause for such a discrepancy.…”
Section: Resultssupporting
confidence: 69%
“…A remarkable decrease of τ av with sintering temperature evidences that a recovery of open-volume defects takes place during sintering. By similarity of present lifetimes with those observed for compacted ZrO 2 +3 mol.% Y 2 O 3 and other similar YSZ nanopowders at the room temperature [7,8] we attribute τ 2 -and τ 3 -components of Table 1 to the annihilation of positrons trapped in vacancy-like defects situated in the space charge layers along the GB's (τ 2 ≈ 0.180 ns) and triple points (τ 3 ≈ 0.375 ns). Based on simple spatial considerations, the intensity ratio I 3 /I 2 was found to correlate with average grain size d as…”
Section: Apparatus and Data Acquisitionsupporting
confidence: 53%
“…• C is expected to contain also a contribution from positron trapped in defects inside grains known from the investigations on YSZ single crystals [6,8].…”
Section: Apparatus and Data Acquisitionmentioning
confidence: 98%
See 1 more Smart Citation
“…These measurements are supplemented by a coincidence Doppler broadening (CDB) investigation using two HPGe detectors. The nature of defects observed in these materials is discussed on the basis of available experimental data and their comparison with the theoretical calculations of positron lifetimes and high-momentum parts of Doppler profiles, performed [5] within the framework of the atomic superposition method considering appropriate vacancy-type defect configurations. …”
mentioning
confidence: 99%